Alliance portfolios and firm performance: A study of value creation and appropriation in the U.S. software industry - Lavie, Dovev (Strategic Management Journal, 2007)
Abstract This study reveals the multifaceted contribution of alliance portfolios to firms' market performance. Extending prior research that has stressed the value‐creation effect of network resources, it uncovers how prominent partners may undermine a firm's capacity to appropriate value from its alliance portfolio. Analysis of a comprehensive panel dataset of 367 software firms and their 20,779 alliances suggests that the contribution of network resources to value creation varies with the complementarity of those resources. Furthermore, the relative bargaining power of partners in the alliance portfolio constrains the firm's appropriation capacity, especially when many of these partners compete in the focal firm's industry. In turn, the firm's market performance improves with the intensity of competition among partners in its alliance portfolio. These findings advance network research by highlighting the trade‐offs that alliance portfolios impose on firms that seek to manage and leverage their alliances. Copyright © 2007 John Wiley & Sons, Ltd.